The use of taxonomies as a way to achieve interoperability and improved resource discovery in DSpace-based repositories - Ferreira, Miguel (2005)
In this paper, we present the ongoing work being developed at University of Minho in the context of Institutional Repositories, more precisely the ones based on the DSpace platform (developed jointly by the Massachusetts Institute of Technology and Hewlett-Packard). As part of our research, we have created an add-on for DSpace to ensure authority control over the keywords that human cataloguers may use to describe their items of information. These keywords are used by the visitors of the repository for searching and browsing the catalogue. The keywords are organised in a taxonomy that results from the combination of several specialised thesauri, one for each community of users (e.g., Computing, Engineering, Architecture, etc.). Each of these off-the-shelf thesauri is described by a simple XML file. The first thesaurus we have imported into our system was the publicly-available Association for Computing Machinery (ACM) Computing Classification System (CCS). The success of the add-on exceeded our expectations given that there was a broad acceptance by the community of users, probably driven by its simplicity and ease of use. ACM contributed to our work by validating our XML version of the CCS and by publishing it on their Web site. Our most recent endeavour is centred on the conversion of the ACM CCS to OWL (Web Ontology Language). Through the use of taxonomies we expect to achieve better interoperability between analogous systems as well as improve the discovery of resources in our repository. Future work will be focused on the improvement of the add-on to support more complex structures, such as thesauri or ontologies.